Pemanfaatan Bangunan Cagar Budaya di Area Duizen Vierkanten Paal Kota Pontianak sebagai Sumber Pembelajaran Sejarah - Firmansyah, Haris (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2021)
One of the historical relics is a cultural heritage building. Cultural heritage buildings located around student are necessary and important to be introduced to them so that they will be interested in studying history. In the city of Pontianak itself, there are cultural heritage buildings that student need to study as a source of historical learning, namely the cultural heritage buildings located in the Duizen Vierkanten Paal area as a Dutch historical heritage. This study aims to identify the sites of cultural heritage buildings in the Duizen Vierkanten Paal area of Pontianak City and how to use them in learning history at SMA Negeri 3 Kota Pontianak City. This research uses descriptive research with a qualitative approach. Data was collected through literature study, observation, and interviews. The interactive analysis technique of the three components of the analysis used is data reduction, data presentation and conclusion drawing or verification. The results of this study are 1) Duizen Vierkanten Paal is the center of the Colonial government (Eropesche Bestuur) for Westersche Afdeeling van Borneo. There are several cultural heritage buildings left by the Dutch colonial government, including: The Old Bank Indonesia Building (De Javasche Bank Office Pontianak Branch), the Old Post Office (post telegraph office), the Kwarda Pramuka Building West Kalimantan and the Pontianak 14 State Elementary School (Holland Inlandsche School).  2) For the use of cultural heritage buildings located in the Duizen Vierkanten Paal area, teachers can implement it in the form of outdoor learning-based history learning.Salah satu peninggalan sejarah adalah bangunan cagar budaya. Bangunan cagar budaya yang terdapat di sekitar siswa perlu dan penting untuk dikenalkan kepada mereka sehingga meraka akan tertarik untuk mempelajari sejarah. Di Kota Pontianak sendiri terdapat bangunan cagar budaya yang perlu dipelajari oleh siswa sebagai sumber pembelajaran sejarah yakni bangunan cagar budaya yang terdapat di area Duizen Vierkanten Paal sebagai peninggalan sejarah Belanda. Penelitian ini bertujuan untuk mengidentifikasi situs bangunan cagar budaya yang terdapat di area Duizen Vierkanten Paal Kota Pontianak dan bagaimana pemanfaatannya dalam pembelajaran sejarah pada SMA Negeri 3 Kota Pontianak. Penelitian ini menggunakan penelitian deskriptif dengan pendekatan kualitatif. Pengumpulan data dilakukan melalui studi kepustakaan, observasi, dan wawancara. Teknik analisis interaktif dari tiga komponen analisis yang digunakan adalah reduksi data, penyajian data, dan penarikan kesimpulan atau verifikasi. Adapun hasil dari penelitian ini adalah 1) Duizen Vierkanten Paal merupakan wilayah yang pusat pemerintahan Kolonial (Eropesche Bestuur) untuk Westersche Afdeeling van Borneo. Terdapat beberapa bangunan cagar budaya peninggalan pemerintahan Koolonial Belanda yakni antara lain: Gedung Bank Indonesia Lama (Kantor De Javasche Bank Cabang Pontianak), Kantor Post Lama (post telegraf kantoor), Gedung Kwarda Pramuka Kalimantan Barat dan Sekolah Dasar Negeri 14 Pontianak (Holland Inlandsche School). 2) Untuk pemanfaatan bangunan cagar budaya yang terdapat di area Duizen Vierkanten Paal ini guru bisa melaksanakannya dalam bentuk pembelajaran sejarah berbasis Outdoor Learning.